Microbiologic evaluation of efficacy of probiotic for correction intestinal disbiosis - Nelya Bissenova; Aigerim Yergaliyeva; Kaiyrgeldy Makhambetov; Nurkiya Talgatbekova (National Scientific Medical Center, 2016)
Purpose of the study. To determine the microbiological efficacy of probiotics in the intestinal dysbiosis correction in patients with gastroenterological diseases. Methods. A prospective bacteriologic research of intestinal dysbiosis of 47 adult patients (36 women (76.5%), 11 men (23.4%), the average age of 38.0 ± 2.1). The first group consisted of patients with gastroenterological diseases (n = 47). Second group - these same patients after correction with probiotics (n = 23). We conducted qualitative and quantitative analysis of intestinal microbiota both groups. Results. Intestinal microbiocenosis of patients in both groups was included as the obligatory and facultative microflora. In the first group the contents of bifidobacteria in the amount of 108 CFU/g or more was 65.9%, lactobacilli in an amount of 106 CFU/g or higher at 17.0%, E.coli with normal enzymatic activity in an amount of 107 CFU/g or higher in 55.3% of patients, in the second group these indicators were 78.3%, 56.5% and 73.9%, respectively. From facultative microflora in the first group noted the high content of Candida - 4.2%, lactose-negative E.coli - 6.3% and fungi in 8.5% of patients, in the second group these indicators not detected. Conclusion. Thus, the intestinal microflora of patients after correction of probiotics, is characterized by a significant increase in the number of obligate microflora: lactobacilli, bifidobacteria, E. coli with normal enzymatic activity and reduced the number of Candida, lactose-negative E.coli and fungi.